PERENCANAAN FONDASI BORED PILE UNTUK TANAH GRANULER PADA GEDUNG APARTEMEN 10 LANTAI DI BOGOR - Wulan, Asri; Ellysa, Ellysa; Handayani, Tri; M.H, Andi Asnur Pranata; Andayani, Relly; Laksono, Alya Tasya Putri (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The construction of an apartment building that is used as a residential community has stages of construction work that will support the building to remain strong, stable and safe. Planning a building construction can not be separated from the planning of the foundation that must be calculated and designed properly to support the working load without experiencing shear failure and excessive settlement to ensure the stability of the building. The purpose of this plan is to design a bored pile foundation for the construction of a 10 floors apartment in Bogor. Based on the results of soil investigations in the planning area in Bogor, West Java, it was found that the type of soil was dominant granular soil. In the calculation of the foundation planning using a circular bored pile foundation type with a diameter of 0,7 meters at a depth of 18 meters. Calculation of the axial bearing capacity of single and group piles using the Reese & Wright and Converse- Labarre methods. Calculation of pile settlement using the semi-empirical method and the Vesic method. Calculation of lateral bearing capacity using the Broms method. Based on the calculation results, the bearing capacity of the foundation permit is 113,542 tons with the many piles needed as 132 piles. The pile subsidence in the group is 10,770 cm for the 6 pile group and the largest lateral pile deflection is 1,470 mm. The foundation uses 14D19 longitudinal reinforcement and D16-54 shear reinforcement and pile cap dimensions of 1,1 m – 4,5 m with a thickness of 0.9 m. Budget Plan The cost of planning the bored pile foundation for a 10 floors apartment building in Bogor, the total cost is Rp. 3,160,217,000.000 with a foundation price per pile of Rp. 15,626,817.010.